2019
DOI: 10.1111/exd.13945
|View full text |Cite
|
Sign up to set email alerts
|

A novel player in the field: Merkel disc in touch, itch and pain

Abstract: The mechanosensitive Merkel cell‐neurite complex comprising two distinct cell types in both hairy and glabrous skin has been widely recognized as touch receptor for more than 100 years. In 2014, three elegant studies further demonstrated that the Merkel cell‐neurite complex mediates touch transduction via the mechanosensitive Piezo2 channel. However, whether it is involved in genesis of itch and pain sensations, has been unclear. Recently, we reported that Merkel cells modulate the development of mechanical it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 48 publications
(46 reference statements)
2
23
1
Order By: Relevance
“…The role of Aβ-fibres in itch transmission is still disputed. In fact, recent experiments on a psoriasis mouse model suggest that a reduction in Aβ-fibres might contribute to a disinhibition of mechanical itch (20). In the current study only a minority of patients (2.7%) and controls (1.9%) reported itch after electrical stimulation at 2,000 Hz.…”
Section: Discussioncontrasting
confidence: 53%
“…The role of Aβ-fibres in itch transmission is still disputed. In fact, recent experiments on a psoriasis mouse model suggest that a reduction in Aβ-fibres might contribute to a disinhibition of mechanical itch (20). In the current study only a minority of patients (2.7%) and controls (1.9%) reported itch after electrical stimulation at 2,000 Hz.…”
Section: Discussioncontrasting
confidence: 53%
“…54 Similarly, the increased epidermal expression of TRPV1 combined with a decrease of FNEs density in the elderly could question the implication of keratinocyte-sensory neuron synapticlike contacts in senile pruritus. 55,56 Keratinocytes and FNEs may act as a 2-receptor-site model, each conveying specific aspects of temperature, pain, and itch, 10,57 similar to Merkel cells 58 and the Aβ nerve fibers in the Merkel complexes. 24,59 Furthermore, both Merkel cells and keratinocytes express neural differentiation biomarkers associated with reinnervation during human cutaneous repair.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes and FNEs may act as a 2‐receptor‐site model, each conveying specific aspects of temperature, pain, and itch, 10,57 similar to Merkel cells 58 and the Aβ nerve fibers in the Merkel complexes 24,59 . Furthermore, both Merkel cells and keratinocytes express neural differentiation biomarkers associated with reinnervation during human cutaneous repair 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanosensitive pruriceptors are involved in a mechanical induced itch sensation. This touch induced itch sensation involves fading of mechanosensitive Merkel cells with advancing age (alloknesis) [ 380 , 381 ]. Recently, it was shown that the lack of Piezo2 channel signaling (modulator) in Merkel cells is responsible for the conversion of touch into itch sensation [ 382 ].…”
Section: Discussionmentioning
confidence: 99%